2000
DOI: 10.1577/1548-8446(2000)025<0007:ddacso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Distribution, and Conservation Status of the Native Freshwater Fishes of the Southern United States

Abstract: The Southeastern Fishes Council Technical Advisory Committee reviewed the diversity, distribution, and status of all native freshwater and diadromous fishes across 51 major drainage units of the southern United States. The southern United States supports more native fishes than any area of comparable size on the North American continent north of Mexico, but also has a high proportion of its fishes in need of conservation action. The review included 662 native freshwater and diadromous fishes and 24 marine fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
233
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 324 publications
(237 citation statements)
references
References 41 publications
4
233
0
Order By: Relevance
“…Indeed, although differently described species might, in fact, represent single evolutionary lineages, as in the case of lampreys, as much as 28% of the American and Canadian freshwater fish species could be waiting for a formal taxonomic description. This finding reinforces the status of North American fresh waters as harboring some of the world's greatest fish diversity and deserving more important conservation efforts (6). Further DNA barcoding surveys will reveal whether the extremely high proportion of cryptic evolutionary lineages detected in this study is a common characteristic of freshwater organisms.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, although differently described species might, in fact, represent single evolutionary lineages, as in the case of lampreys, as much as 28% of the American and Canadian freshwater fish species could be waiting for a formal taxonomic description. This finding reinforces the status of North American fresh waters as harboring some of the world's greatest fish diversity and deserving more important conservation efforts (6). Further DNA barcoding surveys will reveal whether the extremely high proportion of cryptic evolutionary lineages detected in this study is a common characteristic of freshwater organisms.…”
Section: Resultssupporting
confidence: 77%
“…Despite more than 2 centuries of descriptive taxonomic inquiry, problems inherent to species identification have hampered the study, conservation, and management of the richest diversity of temperate freshwater fish (5). Indeed, the exact amount of diversity is still unknown, and it is thought that 10% of North American freshwater fish are still formally undescribed (6,7). Part of this problem may stem from the fact that there is no universally accepted operational species concept (8,9).…”
mentioning
confidence: 99%
“…Based on lists of imperiled species, fishes adapted to midwater or surface habitats, such as sunfishes (Centrarchidae) and topminnows (Fundulidae), appear to be little affected (Williams et al 1989;Warren and Burr 1994;Etnier 1997). In contrast, benthic fishes, such as species in the families Percidae and Ictaluridae, have been most affected, with over one-quarter of the taxa in each of these groups currently classified as jeopardized (Warren and Burr 1994;Warren et al 2000). In fact, ictalurid catfishes are the most imperiled group of fish-es in the southeastern United States (Warren and Burr 1994) and most of these jeopardized taxa are madtoms (Noturus spp.…”
mentioning
confidence: 99%
“…An earlier review suggested that River Darters were not abundant in Canada [6], with the largest collection at that time being 10 specimens. However, the River Darter is locally abundant in large, turbid rivers in the United States [1,13]. Our surveys resulted in many collections with more than 10 specimens, indicating that River Darters are likely more common in Canadian waters than originally believed.…”
Section: Discussionmentioning
confidence: 90%